Answer:
10 feet
Step-by-step explanation:
you minus the distance between them and the shadow
witch is 20-10 and you will get 10
Answer:
∠ ABC = 90°
Step-by-step explanation:
∠ ABC is the angle in a semi circle and is right, that is
∠ ABC = 90°
Answer:
the first one
Step-by-step explanation:
Answer: It has two pairs of parallel lines
Step-by-step explanation:
coordinates of E (-4,4) K (4,4) M(-6,-3) I( 2,-3)
The distance from E to K is 8 the same as the distance from M to I.
The distance from M to E is about 7.3 and the distance between K and I is the the same thing.
Answer:
Counting the unit on graph, we observes:
EK = MI = 8
EK // MI // x-axis
=> MEKI is parallelogram
Hope this helps!
:)
The slope-intercept format is 'y = mx + b'
Knowing this, we can just input the given values into the format.
y = 6x + 2
If you need me to explain anything in more depth, just ask :))
Good luck!
-T.B.
first laptop: $700
second laptop: $400
third laptop: $200
B.
first laptop: $700
second laptop: $200
third laptop: $400
C.
first laptop: $650
second laptop: $250
third laptop: $400
D.
first laptop: $650
second laptop: $200
third laptop: $450
E.
There is not enough information to solve for the unknowns.
Option: A is the correct answer.
A.
first laptop: $700
second laptop: $400
third laptop: $200
Let the cost of first laptop be: x
Second laptop be: y
and cost of third laptop be: z
Now, it is given that:
Adam bought three laptops for his office at a total cost of $1,300.
This means that:
x+y+z=1300---------(1)
on doubling the price of the first laptop and tripling the price of the third laptop, the total cost increased to $2,400.
This means that:
2x+y+3z=2400-------(2)
He spent $100 more on first laptop than the combined price of the second and third laptops.
This means that:
x-(y+z)=100------------(3)
On using equation (1) we have:
y+z=1300-x
Keeping the value of y+z in equation (3) we get:
x-(1300-x)=100
x-1300+x=100
2x=100+1300
x=1400/2=700
Hence, price of first laptop is: $ 700.
Now on putting the value of x in equation (1) and (2) we get:
y+z=600 ⇒ y=600-z------(4)
and y+3z=1000 (from equation (2) )
⇒ 600-z+3z=1000
⇒ 600+2z=1000
⇒ 2z=1000-600
⇒ 2z=400
⇒ z=200
Hence, cost of third laptop is: $ 200
and cost of second laptop is: $ 400
( since on putting the value of z in equation (4) )
A.
first laptop: $700
second laptop: $400
third laptop: $200